Evaluation of Hematological Parameters And DHEA-S Hormone Association with Acne In The Province Of Thi-Qar - Ayat S. Saleh1 Ali N. Salman2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This study was conducted in the labs of the College of Education for Pure Sciences, Al-Hussein Educational Hospital and Al-Nahrain Specialized Laboratory of the Health Department of Thi-Qar province, during the period from October 2018 to March 2019. The study included of 100 blood sample of patients with acne (39 males) and (61 females) and their age between 10-35 years. The aim of the study was to assess the level of DHEA-S hormone in acne vulgaris patients in the serum using a technique enzyme- linked immunosorbent Assay (ELISA).The study included the test of the susceptibility of phagocytic cells on phagocytosis (coefficient of phagocytosis) and measurement of hematological parameters (Red blood cell count, hemoglobin ratio, total and differential white blood cells count).The results showed the presence elevate in the level of DHEA-S for 21 sample out of 70 patients with acne. Results showed that there was no association between disease incidence and DHEA-S when compared with the healthy control in the population of Thi- Qar province.Increase coefficient phagocytosis was significant (P? 0.05) in all patients with acne compared with a group of control. As for the blood parameters, the results of the present study showed no significant differences (P?0.05) in the rates of red blood cells and hemoglobin in all acne patients compared to the control group. It also showed increased rate of counting the total of WBCs and differential cell neutrophils and lymphocytes (P?0.004), (P?0.004),(P?0.025), respectively in acne patients compared to healthy controls group.